Organizational transformation and managing innovation in the fourth industrial revolution - Guerra Guerra, Alicia, 1963- (IGI Global, 2019)
"This book explores the new economy initiating the fourth industrial revolution: a social, environmental and technological transformation which, therefore, decisively influences the mission and vision of public and private organizations, both for profit and non-profit, in the innovative manners in which they should be managed, so as to seek their ideal positioning and, even, their survival"--